Awareness of Breast Cancer Risk Factors and Practice of Breast Self-Examination Among Nursing Students - Mona H. Afif (Evidence-Based Nursing Research)
Contents: Breast cancer is the most common cancer in women of both developed and less developed world. Breast cancer is a common malignancy among Saudi females, with a prevalence of 21.8%. Awareness of risk factors and practice of breast self-examination still has a significant role in the early detection effort of breast cancer, particularly in young women.